Risk and sustainable crop intensification: The case of smallholder rice and potato farmers in Uganda - Van Campenhout, Bjorn; Bizimungu, Emmanuel; Birungi, Dorothy (International Food Policy Research Institute, 2016)
To feed a growing and increasingly urbanized population, Uganda needs to increase crop production without further exhausting available resources. Therefore, smallholder farmers are encouraged to adopt sustainable crop intensification methods such as inorganic fertilizer or hybrid seeds. However, these farmers perceive these new technologies as risky hence adoption will depend on how well they can manage this additional risk. This paper documents patterns observed in socioeconomic data that suggest risk is an important barrier to sustainable crop intensification practices among Ugandan smallholder rice and potato farmers. In particular, we find that households that engage in risk management strategies, such as investing in risk-reducing technology or engaging in precautionary savings, are more likely to practice intensified cropping. However, our data also show only limited yield risk associated with the use of fertilizers or pesticides, suggesting part of the problem is related to perception. We also discuss the consequences for policy.